Environmental and occupational risks to reproductive health in women service members and veterans - Clark, Kendra L. (Frontiers in Public Health, 2025)
Women have played a vital role in the U.S. military for decades, with their presence steadily increasing. However, despite this growth, research on the unique occupational and environmental exposures they face remains limited, highlighting the need for greater understanding to improve reproductive health outcomes. Chemical exposures such as burn pit emissions, airborne particulates, heavy metals, and pesticides can disrupt hormone regulation and pose risks for fertility, miscarriage, preterm birth, and congenital anomalies. Additional risks include unsafe water sources, contaminated soil, increased vaccinations, and extreme environmental conditions. However, studies on these exposures remain inconsistent, with some indicating significant reproductive risks while others show minimal or no impact. This mini review highlights what is currently known about the impact of military-related environmental and occupational exposures on women’s reproductive health and identifies key gaps in the literature. Further research is essential to determine high-risk exposures, guide policy development, and support early intervention strategies. Addressing the long-term impact of military-related environmental exposures is crucial for ensuring better health outcomes and facilitating access to care for female service members and veterans.